2016
DOI: 10.20944/preprints201609.0094.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Destabilization Mechanism of Ionic Surfactant on Curcumin Nanocrystal against Electrolyte

Abstract: Abstract:We have successfully developed curcumin nanosuspension aimed for oral delivery. The main purpose is to improve bioavailability through enhancing its solubility. The nanoparticles were stabilized using various stabilizers including polyvinyl pyrrolidone (PVP), polyvinyl alcohol (PVA), sodium carboxymethylcellulose (Na-CMC), d-alpha tocopheryl polyethylene glycol 1000 succinate (TPGS), and sodium dodecyl sulfate (SDS). The average diameter of particles, microscopic appearance, and sedimentation of each … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The larger size of the quercetin-loaded nanoparticles compared to the empty nanoparticles can be considered as an indicator of the efficient and effective encapsulation of quercetin by the PCL nanoparticles. In the previous studies, it was stated that the drug-loaded nanoparticles can be larger in size compared to the empty nanoparticles (28,29). It was found that, particularly in cancer research, carrier systems smaller than 500 nm are more successful in delivering the drugs to the target tissues, therefore enabling active transport (30).…”
Section: Discussionmentioning
confidence: 99%
“…The larger size of the quercetin-loaded nanoparticles compared to the empty nanoparticles can be considered as an indicator of the efficient and effective encapsulation of quercetin by the PCL nanoparticles. In the previous studies, it was stated that the drug-loaded nanoparticles can be larger in size compared to the empty nanoparticles (28,29). It was found that, particularly in cancer research, carrier systems smaller than 500 nm are more successful in delivering the drugs to the target tissues, therefore enabling active transport (30).…”
Section: Discussionmentioning
confidence: 99%